INFLUENCE OF DEEP CRYOGENIC TREATMENT AT ABRASIVE WEAR RESISTANCE IN ASTM 743 CA6NM - Hernandez, A. F.; Silva, C. R. M.; Araujo, J. A.; de Mello, J. D. B. (Revista de Engenharia Térmica, 2013)
The Deep Cryogenic Treatment (DCT) has been used for improvement of steel mechanical properties, basically the abrasive wear resistance. At this work the cryogenic treatment at -190oC for 20 hours was applied, after conventional heat treatment, to improve its abrasive wear resistance. The specimens, divided in two groups, had been austenitized for forty five minutes at 965oC and 1065oC, respectively, then quenched in oil at room temperature. Afterwards they were tempered at 565oC for 90 minutes, and then cooled in air. Subsequently some samples were treated cryogenically, and some of them were submitted to a new cycle of tempering at 565oC for 90 minutes. The performed experiment included: hardness brinell, Xraydifratometry, metallography and micro-abrasive wear test. Variations in the microstructure with an improvement in the abrasive wear coefficient were found. These variations are probably a positive effect of the DCT on the samples microstructure. The microstructure were transformed from blocks of parallel lath martensite to small parallel or almost parallel packages of fine needles forming austenite. Traces of previous or retained austenite were found delimiting the grains. It is presumed that micro-carbide homogeneously distributed in the matrix and in the grain´s contours of the retained austenite was formed.